THE IMPACT OF DIGITAL MARKETING ON BUSINESS PERFORMANCE THROUGH THE ROLE OF COMPETITIVENESS IN MSMES IN SEMARANG REGENCY - Endang Kustami; Luthfy Purnanta Anzie; Isa Al Ansori; Putri Nurusyifa (ITB AAS Indonesia Surakarta, 2025)
Digital marketing has been identified as a potential strategy to promote MSMEs and sell their products. The objective of this research is to test the influence of digital marketing on business performance with competitiveness as a mediating variable. The study respondents in this sample were 200 MSMEs in Semarang Regency, Central Java Province. The sampling procedure adopted a purposive sampling approach. The closed-end questionnaire was utilized to collect data with a five-point Likert scale. The analysis data method of this study is carried out based on the path analysis using SmartPLS software version 4.1.1.2. The study findings reveal that there is a significant impact of digital marketing on competitiveness. The second one is that digital marketing has a positive impact on business results. Third, the mediating relationship analysis illustrates that the competitiveness variable can mediate the impact of digital marketing on business performance. Research implications are the practical ideas for micro-entrepreneurs of meatball culinary businesses in applying digital marketing, competitiveness, and business performance.